86. Efficacy of botulinum toxin on pain and spastic gait disorders in multiple sclerosis. Issue 1 (January 2015) - Guerriero, R.; Amadio, S.; Butera, C.; Bianchi, F.; Vimercati, O.; Cursi, M.; Martinelli-Boneschi, F.; Comola, M.; Comi, G.; Del Carro, U.
<x xml:space="preserve">Abstract</x> To assess the efficacy of botulinum toxin (BT-A) and additional physiotherapy in subjects affected by progressive multiple sclerosis (MS) with chronic lower limb spasticity. 15 patients able to walk with assistance were consecutively recruited in a open-label study. All patients received a set of intramuscular injections of BT-A performed with EMG-guidance, according to each patient's individual pattern of spasticity, followed by additional physiotherapy. Each patient was assessed at baseline, 6 and 12 weeks for muscle tone, spasms frequency, leg pain, gait velocity, self-analysis of gait function. 7 patients received a further treatment session after 4 months and were retested after 4 and 8 months. We observed a significant (P < 0.05) reduction of muscle tone, spasm frequency and pain and a partial improvement of gait velocity and function after 6 weeks. The results did not change at 12 week follow-up. The seven patients who received a second set of injections maintained their scores after 4 months e three of them after 8 months. Injections of BT-A, followed by additional physiotherapy, are effective on spasms and pain in patients affected with multiple sclerosis. BT-A injections can otherwise improve gait function for several months in patients able to walk with assistance.